The complete chloroplast genome of Quercus fabri (Fagaceae) from China - Xu, Yang (Mitochondrial DNA B Resour, 2019)
The complete chloroplast (cp) genome sequence of Quercus fabri Hance has been characterized in this study. The length of cp genome was 161,227 bp, containing a large single-copy region (LSC) of 90,539 bp and a small single-copy region (SSC) of 19,048 bp, which were separated by a pair of 25,820 bp inverted repeat regions (IRs). The genome contained 134 genes, including 86 protein-coding genes, 40 tRNA genes, and 8 rRNA genes. The overall GC content is 36.82%. Further, phylogenetic analysis suggested that Q. fabri is clustered to section Quercus.